Development of Presentation Media for Learning Moral Creeds in Improving Student Learning Outcomes - Binti Harun, Zakiah; Muh . Akib H (Al-Iftah: Journal of Islamic studies and society, 2024)
This study discusses the use of presentation media in teaching Aqidah Akhlak in improving student learning outcomes. The method applied is the RnD (Research and Development) research method which uses experimental research with a quantitative approach. This series of research was then carried out with the development of ADDIE (Analysis, Design, Development, Implementation, and Evaluation) research which involved one class group, namely Class XI students at MA Al Qasimiyah Madello, Barru Regency. The ADDIE development pattern is implemented in detail, including through analyzing learning materials, designing the presentation of the material to make it interesting, developing the material by paying attention to student needs, implementing it effectively in the classroom, and then carrying out in-depth analysis of student learning outcomes after the entire series of research has been carried out.This research suggests that the use of presentation media in learning Aqidah Akhlak through the development of ADDIE is able to provide good learning outcomes for students. This is evidenced by the increase in scores which increased significantly from the pre-test stage to the post-test stage. The learning results at the pre-test stage found 15 students with very low scores, 1 person in the low category, and 2 people in the medium category. Which means that no one whose score is above the KKM standard is declared incomplete. This condition changed significantly at the post-test stage so that as many as 17 students were in the high category and there was even 1 person whose learning results were in the very high category. Thus, it can be concluded that the effectiveness of the combination of ADDIE development with the application of presentation media is very effective in improving student learning outcomes in Aqidah Akhlak learning so that it can become an innovation in Islamic Religious Education learning to make it more enjoyable.